Pemberdayaan masyarakat melalui keterampilan vokasional dalam memanfaatkan limbah plastik sebagai pengembangan seni kerajinan di Kabupaten Takalar - Mantasia Mantasia; Sapto Haryoko; Saliruddin Saliruddin; Hendra Jaya (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The empowerment activity was carried out for two months in Aeng Batu-batu village, Galesong Utara District, Takalar Regency, South Sulawesi Province. Proposed solutions to problems specifically in the making of woven craft crafts based on plastic waste. The steps taken in the implementation of this empowerment can be stated as follows: 1) Departure to the location of KKN, Aeng Batu-Batu village, North Galesong sub-district Takalar; 2) Student socialization to community leaders on the main theme of empowerment and to obtain additional input and information that can be used as support programs; 3) Implementation of the program with the method of reflection, discussion, field practice and making tools; 4) Counseling Activities Making woven craft crafts based on plastic waste. Community awareness increases in loving and protecting the environment, especially in the coastal areas of Aeng Batu - Batu Village, North Galesong District, Takalar Regency. Various types of trash can be used as decoration knick knacks.